Economic causes of deforestation in the Brazilian Amazon: A panel data analysis for the 2000s - Jorge Hargrave; Krisztina Kis-Katos (University of Freiburg, Department of International Economic Policy (iep), 2011)
We use under-explored municipality level datasets to assess the recent economic and policy determinants of deforestation in the Brazilian Amazon. We estimate yearly panel data models (from 2002 to 2009) for 457 municipalities in the region. The results show that recent deforestation is related to economic incentives, and especially to fluctuations in product (meat and soybean) prices. Moreover, we document that the increasing monitoring efforts of the Brazilian environmental police (IBAMA) were effective in reducing deforestation rates.
Keywords: Q56; 330; Causes of deforestation; Amazon; Brazil; Entwaldung; Ökonomischer Anreiz; Agrarpreis; Volatilität; Umweltpolitik; Amazonas (Fluss); Brasilien